High-fat diet during sexual maturation induces hyperplastic differentiation of rat prostate and higher expression of AR45 isoform and ERα - Pytlowanciv, Eloisa Zanin [UNESP]; Ribeiro, Daniele Lisboa; Tamarindo, Guilherme Henrique [UNESP]; Taboga, Sebastião Roberto [UNESP]; Góes, Rejane Maira [UNESP] (Elsevier, 2022)
We examined the consequences of high-fat diet (HFD) on prostate histophysiology in two periods along sexual maturation of rats and the impact on the gland in adulthood. After weaning, male Wistar rats were fed a balanced diet (4 % fat-C3, C6, C9) or a HFD (20 % fat- HF3, HF6, HF9) for 3, 6 or 9 weeks. Fat deposit weights, blood glucose and levels of serum testosterone and estrogen were measured. Prostate was evaluated for histology, proliferative and apoptotic cell index, and for the expression of androgen (AR), estrogen receptors type α (ERα) and aromatase. HFD did not affect estrogen levels and elevated serum testosterone only in HF9. HFD reduced prostate weight in HF6 and increased it in adulthood (HF9) but relative prostate weight was unchanged among groups. Cell proliferation, height and density were higher in epithelium of all HFD-groups, compared to controls, featuring the epithelial hyperplasia. Epithelial apoptosis was lower in HF9. HF3 and HF9 exhibited higher expressions of ERα, indicating that HFD triggers a new activation of ERα expression in the acinar epithelium. The content of prostatic aromatase was also elevated in HF9. Increased numbers of AR-positive cells were observed in all HFD groups, and western blotting analysis showed an increase in the truncated form of 45 kDa (AR45) and a reduction in the expression of 110 kDa-AR for HF3 and HF9. In conclusion, excessive dietary fats during sexual maturation of rats led to developmental programming of the prostate, inducing a hyperplastic status with perturbations in AR isoforms expression and reactivation of ERα in adulthood, whose implications for posterior prostatic health could be detrimental.
Keywords: Androgen receptor isoform; Estrogen receptor alpha; High-fat diet; Prostate hyperplasia; Sexual maturation